ANALISIS PERENCANAAN DAN REALISASI KEUANGAN PADA PERUSAHAAN PT. GLOBAL RANCANG SELARAS: ANALISIS PERENCANAAN DAN REALISASI KEUANGAN PADA PERUSAHAAN PT. GLOBAL RANCANG SELARAS - Mohammad Ardiyanto (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
This research aims to analyze the suitability of the realization of financial planning as a manifestation of internal control and Corporate Accountability at PT Global Rancang Selaras. The analysis method used by the author in this study is through data collection by direct interviews with the Company's finance department and the Company's financial data that is permitted to be researched. The research period was carried out based on financial reports and records in 2024. The results of the research conducted showed that in the planning realization process there were several problems such as the emergence of expenditure items that were not included in the planning, the replacement of items from the planning, to the urgent need for smooth operations. This research is expected to provide input to the Company so that the planning function can be optimal and facilitate internal control